Experiencing the art of theatre - Downs, William Missouri (Thompson Wadsworth, 2007)
This invigorating new introductory text makes timely and relevant connections between theatre and the familiar world of Hollywood television and film to help students understand how the living art of theatre relates to, predates, and influences the screen entertainment they are used to watching. From theatre's ritual origins to modern musicals, from the controversies surrounding the NEA to the applicability of acting lessons in everyday life, this book is an important first step toward a deeper awareness of theatre's continuing and contemporary significance. Featuring strong coverage of current events in theatre, the reviewer-praised anecdotal narrative makes this book fun to read and one that students will want to keep long after the course is over. THE ART OF THEATRE is organized into three distinct sections, giving you the flexibility to organize your course your way. Adding to this flexibility is the book's availability in two versions. THE ART OF THEATRE: THEN AND NOW contains 16 chapters with extensive coverage of the history of theatre. EXPERIENCING THE ART OF THEATRE: A CONCISE INTRODUCTION features 13 chapters and a briefer treatment of theatre history